Professionnalisation des enseignants et démocratisation scolaire : une formation initiale pensée à l’aune de la réduction des inégalités scolaires ? - Claire Benveniste (Éducation et Socialisation)
In this article, we seek to compare the "offer of professionalization" in initial training to the dynamics of socialization and professional development of beginning primary school teachers, in the light of their of their difficulties to teach a part of their students, mostly from popular backgrounds. Our study is based on interviews conducted with trainee teachers at the end of their training, the national official texts framing the teacher training, the models and descriptions of the MEEF master courses, the supports and the course notes in several ÉSPÉs. The data show that initial education largely conceals or isolates the contributions of research that apprehends the teaching practices and difficulties of students as socially constructed and situated. Despite orders to implement "good practices", considered "effective", or even democratizing, primary school teachers ultimately have few resources to act on the conditions of equal access for all to school knowledge.